A comparative absorption study of sucrosomial® orodispersible vitamin D3 supplementation vs. a reference chewable tablet and soft gel capsule vitamin D3 in improving circulatory 25(OH)D levels in healthy adults with vitamin D deficiency—Results from a prospective randomized clinical trial - Bano, Aasiya; Abrar, Saida; Brilli, Elisa; Tarantino, Germano; Bugti, Ali Akbar; Fabbrini, Marco; Conti, Gabriele; Turroni, Silvia; Bugti, Mahroo; Afridi, Fauzia; Mureed, Shah; Zada, Hakeem; et al. (Frontiers in Nutrition, 2023)
Vitamin D (Vit D) deficiency (VDD) associated with diverse health conditions, is commonly treated with Vit D3 supplements. However, the gastrointestinal (GI) absorption (efficacy) of Vit D3 different formulations has not been well studied.We aimed to compare the efficacy of an innovative phospholipids-sucrester matrix biodelivery vehiclebased (sucrosomial) orodispersible Vit D3 preparation against a reference chewable tablet and soft gel capsule (SGC) Vit D3 formulations in Vit D deficient healthy adults.In study 1, 25 subjects were randomised to receive a weekly single dose of 200,000 IU of sucrosomial Vit D3 (n=12) or chewable tablet Vit D3 (n=13) for three weeks. In study 2, 20 subjects were randomised to receive a single dose of 200,000 IU every other week of sucrosomial Vit D3 (n=10) or SGC Vit D3 (n=10) for six weeks. Circulatory 25-hydroxyvitamin D3 (25(OH)D) levels were reassessed after two, three and six weeks in study 1, and four-and six weeks in study 2.In study 1, after two weeks, circulatory 25(OH)D levels increased significantly in both Vit D3 groups (p < 0.0001) but improved markedly in sucrosomial group, with no further considerable change after three-and six-weeks in both groups. Overall, at all three follow-ups sucrosomial Vit D3 achieved significantly higher and sustained 25(OH)D levels (p < 0.001). In study 2 after four-weeks, both Vit D3 treatment groups showed significant improvement in 25(OH) levels (p < 0.0001) but substantially higher in sucrosomial group with statistically significant difference between the two groups (p = 0.02). At six-weeks follow-up, only subjects in sucrosomial Vit D3 group showed a further increase in 25(OH)D levels (p = 0.049), but no further significant changes in levels of SGC Vit D3 group (p = 0.062), showing statistically significant difference between the two groups (p = 0.002). The Vit D3 treatment was well tolerated by all participants and no treatment-emergent effects or serious adverse events were reported.Our results suggest that the sucrosomial Vit D3 preparation absorbs efficiently in the GI system, achieving adequately higher and sustained circulatory Vit D levels in VDD, and thus can effectively contribute to protection against VDD-associated health conditions.